Intra-articular injection of kartogenin-conjugated polyurethane nanoparticles attenuates the progression of osteoarthritis - Wenshuai Fan; Jinghuan Li; Liu Yuan; Jifei Chen; Zhe Wang; Yiming Wang; Changan Guo; Xiumei Mo; Zuoqin Yan (Taylor & Francis Group, 2018)
Osteoarthritis (OA) is the most common form of joint disease and a leading cause of physical disability, there is an urgent need to attenuate the progression of OA. Intra-articular (IA) injection is an effective treatment for joints diseases, however, the therapeutic effects mostly depend on the efficacy of drug duration in joints. Drug delivery system can provide drug-controlled release and reduce the number of IA injection. In this study, amphiphilic polyurethanes with pendant amino group were synthesized and amide bonds were formed between the amine group of polyurethane and the carboxyl group of kartogenin (KGN), a small molecular reported to show both regenerative and protective effects on cartilage. Our results showed that KGN-conjugated polyurethane nanoparticles (PN-KGN) were spherical and regular in shape with an average size of 25 nm and could sustained and controlled release of KGN in vitro. PN-KGN showed no cytotoxicity and pro-inflammatory effects on chondrocytes. The therapeutic effects in OA model showed that IA injection of KGN could attenuate the progress of OA, however, the cartilage degeneration became obviously at 12 weeks with matrix loss and vertical fissures. By contrast, IA injection of PN-KGN showed less cartilage degeneration with significant lower OARSI scores even at 12 weeks, indicating PN-KGN could further arrest the development of OA. Immunohistochemistry also validated that IA injection of PN-KGN retained the normal compositions of cartilage matrix, with much stronger Col II staining and less Col I staining. In conclusion, IA injection of PN-KGN is a better potential strategy to treat OA, with long-time cartilage protection and less IA injections.